How Regulatory Focus Impacts the Process-by-Outcome Interaction for Perceived Fairness and Emotions - Cropanzano, R. (Institutional Knowledge at Singapore Management University, 2008)
Judgments of fairness take into account at least two pieces of information--the outcome received and the process by which the outcome was assigned. Generally speaking, low levels of fairness are apt to be reported when the outcome is unfavorable and the allocation process is deemed inappropriate. In this study, we investigate how regulatory focus theory can further our understanding of the process by outcome interaction. Specifically, when individuals are working to add to their earnings (a promotion focus) the typical effect is observed. However, when individuals are focused on maintaining something that is their own (a prevention focus) the most negative emotion occurs when individuals are allocated an unfavorable outcome through a process that contains procedural safeguards.